Determining the carbon transport time from Scots pine (Pinus sylvestris L.) needles to ectomycorrhizal sporocarps using the natural abundance carbon isotopic composition - Mo, Lan; Salmon, Yann; Lehmann, Marco M.; Hobbie, Erik A.; Schiestl-Aalto, Pauliina; Sahlstedt, Elina; Tang, Yu; Bienz, Siiri; Young, Giles H.F.; Rinne‐Garmston , Katja T. (Oxford University Press, 2025)
Ectomycorrhizal (ECM) fungi, as major carbon (C) sinks, are critical to plant–soil C cycling. Although C allocation between plants and ECM fungi has been studied extensively, C transport time, the key component of C cycling, remains poorly understood. To address this, we collected new needles (weekly), roots (monthly) and ECM fungi (sporocarps and hyphae) of three genera (Cortinarius, Lactarius and Russula) in a boreal Scots pine (Pinus sylvestris L.) forest in Finland. We analysed the natural abundance C isotope composition (δ13C) of sugars or organic matter and observed a strong vapour pressure deficit (VPD) signal in needle sucrose δ13C. We coupled VPD with the δ13C of water-soluble carbohydrates (WSC, δ13CWSC) in sporocarps to determine C transport times. We found Lactarius and Russula, with short hydrophilic mycelia that enable efficient solute uptake, had transport times of 6–13 days, peaking at 8 days. In contrast, Cortinarius, with extensive hydrophobic mycelia that limit water and solute movement, showed slower transport times of around 18 days. The different transport time is likely attributable to a more extensive mycelial network and potentially higher C demand in Cortinarius compared with Lactarius and Russula. The three genera also showed a marginally significant effect on δ13CWSC in sporocarps (P = 0.06, analysis of covariant). This study highlights that natural abundance δ13C analysis offers a practical alternative to pulse-labelling for estimating C transport time in complex plant–fungal interactions, where the latter is difficult to implement. The longer transport time of Cortinarius compared with Lactarius and Russula is critical during periods of reduced photosynthesis, when limited C supply makes fast allocation essential for sustaining belowground metabolism. Slower transport may weaken its role and reduce forest productivity in boreal forests with short growing seasons. As global warming favours Cortinarius, its longer C transport time may impede soil C cycling and nutrient turnover.
Keywords: C allocation; C isotopes; intra-season δ13C dynamics; time lag; transport sugar; water-soluble carbohydrates